Messages of Nationalism and the Motivation to Return to Indonesia: A Critical Discourse Analysis of Sri Mulyani Indrawati's Lectures to LPDP Awardees - Akhmad Mukhibun; Andayani; Raheni Suhita; Ahimsa W Swadeshi; Khusnul Fatonah; Alifah Raihan Nur Hasanah (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
A speech or lecture plays a role in influencing one's perceptions, internalising values, and persuading people's will. This study aims to explore the textual and societal analysis that underpin the discourse of Sri Mulyani Indrawati's lectures during the Departure Preparation for LPDP scholarship awardees. This research used Teun A. Van Dijk's critical discourse analysis approach. The data sources used are two videos of Sri Mulyani Indrawati’s lectures on the YouTube channel of LPDP RI and news searches in the mass media. The results of this study are as follows. First, the macrostructure in the lectures is the theme "Building Human Resources with Integrity and Global Competitiveness Quality" and "Reflection of the Red and White: I Go to Return". Second, the superstructure is in the form of a lecture scheme, starting from opening, body, closing, questions and answers, to final closing. Third, the microstructure components are background (27% and 23%), details (20% and 23%), explicit intent (20% and 23%), implicit intent (3%), presuppositions (37.5% and 26% ), active sentences (92% and 96.5%), passive sentences (8% and 3.5%), coherence (13% and 28%), conditional coherence (56% and 38%), differentiating coherence (3%), and word replace (25% and 25%), English lexicon, expression of enthusiasm and pride, and 14 metaphors. Fourth, the societal analysis in the lecture indicates the situation faced by Indonesia, such as issues of integrity/honesty, the decline in Indonesia's competitiveness, and the non-return of LPDP scholarship awardees.   Pidato atau ceramah memiliki peranan mempengaruhi persepsi seseorang, menginternalisasi nilai, hingga mempersuasi kehendak masyarakat. Penelitian ini bertujuan untuk mendeskripsikan wujud analisis teks dan analisis sosial yang membangun wacana ceramah Sri Mulyani Indrawati pada kegiatan Persiapan Keberangkatan para penerima beasiswa LPDP. Penelitian ini menggunakan pendekatan analisis wacana kritis Teun A. Van Dijk. Sumber data yang digunakan berupa dua video ceramah Sri Mulyani Indrawati pada akun YouTube LPDP RI dan penelusuran berita di media massa. Hasil penelitian adalah sebagai berikut ini. Pertama, wujud struktur makro yang ditemukan adalah tema “Pembentukan SDM Berintegritas dan Berdaya Saing Global” dan “Refleksi Merah Putih: Aku Pergi untuk Kembali.” Kedua, wujud superstruktur berupa skema ceramah, yakni pembuka, isi, penutup, tanya jawab, dan penutup akhir. Ketiga, komponen struktur mikro berupa latar (27% dan 23%), detail (20% dan 23%), maksud eksplisit (20% dan 23%), maksud implisit (3%), praanggapan (37,5% dan 26%), kalimat aktif (92% dan 96.5%), kalimat pasif (8% dan 3.5%), koherensi (13% dan 28%), koherensi kondisional (56% dan 38%), koherensi pembeda (3%), dan kata ganti (25% dan 25%), leksikon berbahasa Inggris, ekspresi semangat dan bangga, serta 14 metafora. Keempat, wujud analisis sosial berupa situasi yang dihadapi Indonesia, seperti persoalan integritas/kejujuran, turunnya daya saing Indonesia, dan ketidakpulangan penerima beasiswa LPDP.